List of subscribers as the source of data on book history and the history of reading: case study of book subscribers' lists printed in Dalmatia in the early 19th century (Libellarium: journal for research in the field of information and related sciences, 2013)
Customer networks or lists of subscribers as a new publishing phenomenon first occurred in Dalmatia in the early 19th century. It was a model of collective funding of book, magazine and newspaper publishing, which gradually replaced the earlier system of individual patronage. It resulted in the publication of lists of subscribers that contained the names of all those who financially supported the printing of a book. The data on names of subscribers, their occupation, place of residence and number of copies ordered, which was the usual content of subscribers, lists, make them very valuable sources for research on the history of books and reading. This paper tries to show the research potential of such lists by presenting a case-study of five preserved and available subscribers' lists found in publications printed between 1835 and 1848 in the Zadar print shop of Battara brothers. The paper analyses the quantitative data on subscribers, their geographical distribution, professional profile and gender, which does not exhaust their research potential in full. The analysis has shown that despite the austere educational opportunities, high incidence of unemployment, and many other limitations, there were people who treasured the written word. The subscribers mostly came from coastal cities like Zadar, Split and Dubrovnik, which were the most important publishing and cultural centres. Even though the subscribers came from Austria, Military Border, Italy, Croatia proper and Slavonia, as well as Bosnia and Herzegovina, which was then part of the Ottoman Empire, they make up only one eight of the total number of subscribers in the corpus. The subscribers are both Roman-Catholic and Orthodox, who mostly subscribed to books printed in the Cyrillic script. The subscribers come from a wide range of professions, mostly from the church circles in Dalmatia, and the fewest of them were professors and teachers, members of the army and the police. As expected, salesmen, due to the nature of their profession and frequent travel, were recorded mostly in Austria, Military Border and the Ottoman Empire. Different groups of subscribers subscribed to different books, depending on the language, topic, or the author. Finally, the gender distribution results bear witness to the inequalities women experienced in 19th century – the share of women was only 1%.We can conclude that even though lists of subscribers are not in themselves sufficient for making informed conclusions on the readership in the early 19th century, they can definitely contribute towards its better understanding. The aim of this paper was to indicate their relevance as source of information on the process of production, distribution and reception of the written word in the 19th century.
Keywords: subscription; collective patronage; 19th century; Dalmatia